Fully adiabatic 31P 2D‐CSI with reduced chemical shift displacement error at 7 T — GOIA‐1D‐ISIS/2D‐CSI1. Issue 5 (19th June 2012) - Chmelík, M.; Just Kukurová, I.; Gruber, S.; Krššák, M.; Valkovič, L.; Trattnig, S.; Bogner, W.
Abstract A fully adiabatic phosphorus (31P) two‐dimensional (2D) chemical shift spectroscopic imaging sequence with reduced chemical shift displacement error for 7 T, based on 1D‐image‐selected in vivo spectroscopy, combined with 2D‐chemical shift spectroscopic imaging selection, was developed. Slice‐selective excitation was achieved by a spatially selective broadband GOIA‐W(16, 4) inversion pulse with an interleaved subtraction scheme before nonselective adiabatic excitation, and followed by 2D phase encoding. The use of GOIA‐W(16, 4) pulses (bandwidth 4.3–21.6 kHz for 10–50 mm slices) reduced the chemical shift displacement error in the slice direction ∼1.5–7.7 fold, compared to conventional 2D‐chemical shift spectroscopic imaging with Sinc3 selective pulses (2.8 kHz). This reduction was experimentally demonstrated with measurements of an MR spectroscopy localization phantom and with experimental evaluation of pulse profiles. In vivo experiments in clinically acceptable measurement times were demonstrated in the calf muscle (nominal voxel volume, 5.65 ml in 6 min 53 s), brain (10 ml, 6 min 32 s), and liver (8.33 ml, 8 min 14 s) of healthy volunteers at 7 T. High reproducibility was found in the calf muscle at 7 T. In combination with adiabatic excitation, this sequence is insensitive to the B1 inhomogeneities associated with surface coils. This sequence, which is termed GOIA‐1D‐ISIS/2D‐CSI (goISICS), has the potential to be applied in both clinical research and in the clinical routine. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.